Effect of Cr, Ni, Cu and Zn in clinker on physical properties of cement via co-processing in a pilot-scale rotary cement kiln - Jenwit Krobthong (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2011